Post corona virus Disease-19 (COVID-19): Hyper inflammatory syndrome-associated bilateral anterior uveitis and multifocal serous retinopathy secondary to steroids - Srinivasan Sanjay; Vijay K R. Rao; Deepashri Mutalik; Padmamalini Mahendradas; Ankush Kawali; Rohit Shetty (Indian Journal of Rheumatology)
Coronavirus disease 2019 (COVID-19) pandemic can cause ocular manifestations which include conjunctivitis to retinal manifestations. A 41-year-old Asian Indian male presented with unilateral blurring, glare, and pain in the left eye (LE), 22 days after COVID-19 infection. He had been administered intravenous steroids followed by oral steroids. Eye evaluation showed corrected distance visual acuity of 20/20 in both the eyes (BEs). Anterior chamber showed inflammation in the LE, a day later in the right eye. Fundus examination of the BE showed retinal pigment epithelial changes with serous elevation suggestive of multifocal serous chorioretinopathy. A month later, he had improvement in his symptoms with no cells in BE with topical steroids with resolution of serous retinopathy. Bilateral anterior uveitis possibly represents an immune-mediated trigger of his clinically quiescent psoriasis causing first-ever uveitis episode, possibly due to COVID-19. Serous chorioretinopathy could be secondary to steroids following treatment of COVID-19-related sequelae.